Accelerated versus Standard Rehabilitation after Meniscus Allograft Transplantation in the Knee - Rucinski, Kylee; Stannard, James P.; Crecelius, Cory; Nuelle, Clayton; Cook, James L. (The Journal of Knee Surgery, 2024)
Meniscus allograft transplantation (MAT) is a proven treatment option for patients with symptomatic irreparable meniscus deficiency. When patients are adherent to prescribed postoperative restriction and rehabilitation protocols, outcomes after MAT are considered good to excellent. However, nonadherence to standard protocols is common and can be associated with undesirable outcomes and patient dissatisfaction. Based on demonstrated safety for early weight-bearing following MAT in conjunction with significant advances in graft preservation and surgical techniques, our joint preservation center implemented a shift in practice toward accelerated weight-bearing following MAT and designed this study to test the hypothesis that accelerated rehabilitation would be associated with superior adherence, patient-reported outcomes, and patient satisfaction, without diminishing patient safety, when compared with standard rehabilitation. Patients were included for analyses when they had undergone fresh or fresh-frozen MAT using a double bone plug technique for treatment of medial or lateral meniscus deficiency and had at least 1-year treatment outcomes recorded. The results of this study revealed that patients who were prescribed accelerated rehabilitation after MAT were significantly more adherent than patients who were prescribed standard rehabilitation and reported statistically significant and clinically meaningful improvements in knee pain and function for at least 1-year following MAT, whereas those in the standard cohort did not. While not statistically different, treatment failure rate was lower in the accelerated rehabilitation cohort when compared with the standard rehabilitation cohort (11 vs. 29%). Importantly, initial outcomes for revision MAT were associated with short-term success in all the patients who opted for this option in the study population. These data suggest that accelerated weight-bearing after MAT is safe, promotes patient adherence, and is associated with statistically significant and clinically meaningful improvements in patient-reported knee pain and function at early and mid-term follow-up.
Keywords: meniscus allograft transplantation; weight-bearing; patient-reported outcomes